Cyantraniliprole: A new insecticidal seed treatment for U.S. rice. (February 2021) - Wilson, B.E.; Villegas, J.M.; Way, M.O.; Pearson, R.A.; Stout, M.J.
Abstract: Current pest management practices for the rice water weevil ( Lissorhoptrus oryzophilus Kuschel) and the Mexican rice borer ( Eoreuma loftini Dyar) in U.S. rice rely heavily on a small number of insecticides. Thus, additional products are needed to delay resistance development and replace products no longer available to farmers. Evaluation of novel and widely used insecticidal seed treatments was conducted in eight small plot field trials from 2015 to 2019 in Louisiana and Texas. Treatments evaluated included the insecticides cyantraniliprole, chlorantraniliprole, thiamethoxam, and clothianidin. Seed treated with chlorantraniliprole and seed treated with both cyantraniliprole and thiamethoxam together provided the best control of L. oryzophilus across trials. Thiamethoxam and clothianidin seed treatments did not provide satisfactory control of L. oryzophilus . Only chlorantraniliprole seed treatment controlled E. loftini . Improved yield was recorded from plots treated with chlorantraniliprole or cyantraniliprole + thiamethoxam across trials from 2017 to 2019 over fungicide only controls. Yield differences among treatments were not detected in 2015–2016 trials. Registration of cyantraniliprole seed treatment for use in U.S. rice provides a new tool for diversification of pest management practices and insecticide resistance management. Highlights: Cyantraniliprole seed treatment effectively controlled Lissorhoptrus oryzophilus. Improved control was achieved by cyantraniliprole together with thiamethoxam. Cyantraniliprole was not effective against the stem borer, Eoreuma loftini. Registration of cyantraniliprole provides U.S. rice farmers a new pest management tool.